Towards a novel service learning platform: a second generation learning solution. (1st January 2013) - Simões, Tiago M.C.; Rodrigues, Joel J.P.C.; Costa, Jorge E.F.
The learning experience is constantly evolving and it is supported by recent internet technologies. Nevertheless, some of the available learning solutions still rely on outdated building models and old ideas. Those platforms still fail at some levels because they continue to patch in current concepts, instead of being evolved from scratch. Incorporating new approaches for content delivery, Web 2.0 services, and new ways to reuse learning components, is independent of the learning environment. These solutions may be possible taking into account a conjunction of service-like web services concepts that deploy learning components in e-Learning platforms. In this context, the paper proposes a second generation of the PLEBOX learning platform supplying a service-driven architecture. This paper proposes a novel service based learning platform that provides a powerful on-demand learning resources and a multiple-environment system capable to support a learning decentralised experience. The main contributions of this proposal were deployed, experimented, and validated.